(untitled) - Committee on Science, Engineering, and Public Policy (Washington, D.C., 1995)
On Being a Scientist was designed to supplement the informal lessons in ethics provided by research supervisors and mentors. The book describes the ethical foundations of scientific practices and some of the personal and professional issues that researchers encounter in their work. It applies to all forms of research — whether in academic, industrial, or governmental settings — and to all scientific disciplines
Keywords: Scientists,Research,Research; Vocational guidance,Vocational guidance